POTENTIAL NA-ALGINATE EXTRACT FROM BROWN ALGAE sargassum sp. OF THE MANGO MATURATION PROCESS - Tanti Iriyanti; Abdul Wahid Wahab; Rohani Bahar (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2018)
Extraction of Na-alginate from Sargassum sp. and its application in ripening mangoes has conducted. This research aimed to determine the mango storage period by using sodium alginate solution as edible coating  and optimum concentration that has maximum inhibition power to the maturation the mango. The FTIR result shows that sodium alginate by the result ofthe extraction has the same similar functional group to the sodium alginate in the factory. Quantitative analysis show that content of sodium alginate as the result of the extraction is 22,42%, sodium alginate solution is 1% has pH 10,97 and the viscosity is 90 cps, the water measure of sodium alginate is 11,27% with the measure of ash is 41,47%. By testing the ability of sodium alginate conducted on mango with submersion method in the solution concentration from 0-50 ppm. At a concentration of 20 ppm solution shows that the maximum of storage period is about 15 days at room temperature while without submersion is just about 5 days. By this study, we indicate that sodium alginate potentially as coating fruit preservation.